(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Methods are a crucial aspect of any research study or project. They outline the procedures and techniques used to collect and analyze data, as well as the overall approach taken to answer research questions or achieve project objectives. The methods section provides a detailed description of the study design, sample selection, data collection instruments, data analysis techniques, and any ethical considerations.